Job satisfaction and burnout syndrome in primary school teachers (Revista de Psicología, 2019)
The job of teaching is not limited to teaching classes, involves running a number of activities such as the care and maintenance of the school, the students’ attention on their diversity, the preparation of teaching materials, the completion and submission of paperwork, insertion into training programs, the relationship with parents of students, the relationship with authorities and peers; implying a hard work, a significant psychic charge on the job. When the motivation and satisfaction for teaching diminishes, when the professional commitment and dedication to teaching are not sufficient to ensure satisfactory performance and cope with different situations of everyday work, increases the probability that the teachers experience psycophysical discomfort and exhaustion.The purpose of this study was to assess the state of job satisfaction of teachers and their impact on the dimensions of burnout syndrome. It worked with a sample of 229 teachers at the primary level, from the provinces of Entre Rios and Buenos Aires. The results indicated a significant effect of job satisfaction on the various manifestations of the syndrome. The teachers most satisfied with his work showed low scores on emotional exhaustion, and obtained high values in the dimension personal accomplishment of the Maslach Burnout Inventory (MBI).
Keywords: Job Satisfaction; Emotional Exhaustion; Depersonalization; Personal Accomplishment; Burnout.